PRESENTATION DOSSIER ARTIFICIAL INTELLIGENCE AND EDUCATION 5.0: TRANSFORMATIONS IN TEACHING AND LEARNING (Interdisciplinary Studies Journal, 2025)
We are living in the contemporary scenario a true springtime of Artificial Intelligence (AI). This is a period of flourishing, in which the convergence of scientific advances, technological maturity, and social demands generates a fertile ecosystem for experimentation, paradigm renewal, and the consolidation of innovative educational practices. Just like the season that announces the cyclical renewal of life, this AI spring symbolizes the possibility of reconstructing and re-signifying formative processes, incorporating emerging technologies without losing sight of the ethical, inclusive, and human foundations that support education as a public good and a fundamental right.The dossier “Artificial Intelligence and Education 5.0: Transformations in Teaching and Learning” emerges from this context as a space for dialogue among different fields of knowledge (Computer Science, Information and Communication Technologies, Human and Applied Social Sciences, Linguistics, Language Studies, and Arts), recognizing that the transdisciplinary nature of AI requires multiple and complementary perspectives. Bringing together theoretical and empirical research and reflections, this collection problematizes not only the technical potential of AI to personalize teaching, analyze educational data in real time, or create immersive environments, but also the ethical, political, and epistemological implications of this integration.
Keywords: Artificial Intelligence; Education 5.0; Transformations; Teaching; Learning